Risk assessment of ergonomic risk factors at construction sites - Jabbarani Torghabeh, Zahra (2013)
Construction as a complex industry challenges the protection of safety and health of workers who are exposed to many risk factors in construction sites. Exposure to these risk factors may develop Musculoskeletal Disorders (MSDs). The study is aimed at prioritizing Ergonomic Risk Factors (ERFs) in order of risk. To achieve the aim of this study, a questionnaire survey was distributed among respondents randomly selected from construction sites in Malaysia. The results of this study indicated that the most critical ERFs are Extreme hot temperature, Leaning forward/side, twisting the back and Organizational factors, while the least critical ERFs are Kneeling positions on hard surfaces, Holding tools with longitudinal ridges on handles tightly and Using hands or knees as a hammer. Identification of ERFs and their risk levels are the results of this study. Successful safety performance and management necessitate the investigation of ERFs and hazards regarding risk levels.